Ara h 2 cross-linking catalyzed by MTGase decreases its allergenicity. Issue 3 (22nd February 2017) - Wu, Zhihua; Lian, Jun; Zhao, Ruifang; Li, Kun; Li, Xin; Yang, Anshu; Tong, Ping; Chen, Hongbing
Abstract : Ara h 2 cross-linking involving linear allergen epitopes significantly decreases its allergenicity. Abstract : Peanuts, whose major allergen is Ara h 2, are included among the eight major food allergens. After reduction using dithiothreitol (DTT), cross-linking of Ara h 2 could be catalyzed by microbial transglutaminase (MTGase), a widely used enzyme in the food industry. In this study, Ara h 2 cross-linking was catalyzed by MTGase after it was reduced by DTT. Using mass spectrometry and PLINK software, five cross-linkers were identified, and five linear allergen epitopes were found to be involved in the reactions. The IgE binding capacity of cross-linked Ara h 2 was found to be significantly lower compared to that of native and reduced Ara h 2. After simulated gastric fluid (SGF) digestion, the digested products of the cross-linked Ara h 2, again, had a significantly lower IgE binding capacity compared to untreated and reduced Ara h 2. Furthermore, reduced and cross-linked Ara h 2 (RC-Ara h 2) induced lower sensitization in mice, indicating its lower allergenicity. Reduction and MTGase-catalyzed cross-linking are effective methods to decrease the allergenicity of Ara h 2. The reactions involved linear allergen epitopes destroying the material basis of the allergenicity, and this might develop a new direction for protein desensitization processes.